High-heat-conductivity diamond / metal joint and brazing method thereof
Through laser processing and vacuum brazing technology, the introduction of periodic micro-nano structures on the diamond surface has solved the problem of insufficient mechanical and heat transfer performance of diamond/metal interface in traditional connection technology, and joints with high thermal conductivity and excellent mechanical properties are achieved to avoid The defects caused by high temperature processing.
Patent Information
- Application Number
- CN202411430981.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-14
AI Technical Summary
Traditional diamond/metal connection technology is difficult to meet the mechanical properties and heat transfer requirements of the interface at the same time, resulting in poor mechanical properties and low thermal conductivity.
Periodic micro-nano structures are drawn on the diamond surface through laser processing, and vacuum brazing is carried out according to the diamond/brazing/metal sandwich structure to increase the effective contact area of the interface, introduce a three-dimensional heat transfer mode, improve thermal conductivity, and pass cracks The deflection effect improves mechanical properties.
The thermal conductivity of diamond/metal joints is improved by 20% and mechanical properties of 30%, while avoiding thermal damage and cracks caused by high-temperature processing, and obtaining uniform and defect-free joint tissue.
Smart Images

Figure CN119260095A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of brazing connection of dissimilar materials, in particular to a high thermal conductivity diamond / metal joint and a brazing method thereof. Background Art
[0002] Diamond has excellent material properties such as low thermal expansion coefficient, high thermal conductivity, isotropic thermal conductivity, low dielectric constant and dielectric loss, and strong radiation resistance, and is considered to be the most promising thermal management material. In order to meet its structural and functional requirements, diamond is often combined with metals or itself. However, most metals cannot wet diamond, or there will be no chemical reaction between them, which is not conducive to the metallurgical bonding of diamond and metal.
[0003] At present, there are several main methods to achieve the interface bonding between diamond and metal. First, direct bonding under high pressure and high temperature, but traditional processing technology is difficult to obtain a good interface and has poor mechanical properties. Secondly, the interface bonding layer is introduced by metallization of the diamond surface, but the current modification processes (such as chemical plating, chemical vapor deposition, magnetron sputtering, etc.) have the disadvantages of interface defects and weak interface strength, so the reliability of the interface and effective heat conduction cannot be guaranteed. The third is the active brazing method. Adding carbide-forming elements such as Ti, Cr, Zr, and W to the brazing metal can achieve the interface bonding of diamond. Various types of active brazing alloys such as Ni-based, Cu-based, and Ag-Cu-based alloys are used for diamond / metal bonding. However, due to the high processing temperature of most active brazing metals, severe thermal damage and microcracks will form inside the diamond, and the mechanical properties are poor. Therefore, in some processing processes, melting point inhibitors such as Sn and In are added to the brazing metal system to effectively reduce the brazing temperature and form a low thermal conductivity interface phase. However, the formation of a low thermal conductivity interface phase will inevitably reduce the heat transfer performance of the diamond / metal joint. In summary, it is difficult for traditional connection technologies to simultaneously meet the mechanical and heat transfer performance requirements of the diamond / metal interface. Summary of the invention
[0004] The problem solved by the present invention is how to solve the problem that the traditional connection technology is difficult to simultaneously meet the mechanical property and heat transfer performance requirements of the diamond / metal interface.
[0005] In order to solve the above problems, the present invention provides a high thermal conductivity diamond / metal joint and a brazing method thereof.
[0006] In a first aspect, the present invention provides a brazing method for a high thermal conductivity diamond / metal joint, comprising the following steps:
[0007] Laser processing of diamond surface to draw periodic micro-nano structures on the diamond surface;
[0008] Brazing material is coated on the surface of diamond with periodic micro-nano structure, fixed in a diamond / brazing material / metal sandwich structure, and vacuum brazing is performed to obtain a high thermal conductivity diamond / metal joint.
[0009] Optionally, before the step of laser processing the diamond surface, the step further includes: cleaning of the base material, the base material includes diamond and metal, the base material is immersed in alcohol and ultrasonically cleaned for 5-10 minutes, and then taken out and dried.
[0010] Optionally, the step of laser processing the diamond surface specifically includes: using a picosecond laser to laser process the diamond surface, wherein the laser spot diameter is 10-40 microns, the processing speed is 10-40 mm / s, the laser power is 0.5-12.5 W, and the repetition frequency is 100-400 KHz.
[0011] Optionally, the periodic micro-nano structure is a micrometer-scale periodic structure or a nanometer-scale periodic structure, and the periodic micro-nano structure includes a periodic micro-groove or hole array or a honeycomb array.
[0012] Optionally, when the solder is in powder form, the solder is mixed with cellulose and dissolved in pine alcohol to form a paste, which is then applied to the surface of the diamond with a periodic micro-nano structure, wherein the ratio of the solder, pine alcohol and cellulose is 2:1:1-3:1:1.
[0013] Optionally, the solder is an active solder, and the solder is silver-copper-indium-titanium or silver-copper-titanium or silver-copper-tin-titanium.
[0014] Optionally, the metal is aluminum or copper.
[0015] Optionally, the step of fixing the diamond / brazine / metal sandwich structure specifically includes: placing the sandwich structure in a mold and applying a pressure of 0.5-4 MPa for fixing.
[0016] Optionally, vacuum brazing specifically includes placing the fixed sandwich structure into a vacuum brazing furnace for heating, wherein the vacuum brazing furnace maintains a vacuum degree of less than 10 -5 , maintain a heating rate of 10-20℃ / min, heat to 400℃ and keep warm for 5-20min, continue to maintain a heating rate of 10-20℃ / min, heat to 640℃-860℃, keep warm for 20-40min, and maintain a cooling rate of 5-10℃ / min to room temperature.
[0017] In a second aspect, the present invention provides a high thermal conductivity diamond / metal joint, which is made by the brazing method of high thermal conductivity diamond / metal joint as described in any one of the above items.
[0018] The beneficial effects of the high thermal conductivity diamond / metal joint and the brazing method thereof of the present invention are: the diamond / metal interface structure is prepared on the diamond surface by laser processing, which increases the effective contact area of the diamond / metal interface, similar to the introduction of a heat sink structure at the interface, and can achieve more efficient heat transfer at the interface. In addition, laser processing introduces a periodic micro-nano structure in the diamond ablation area during the scanning process, so that when phonons are reflected at the interface of heterogeneous materials, the side wall of the micro-nano structure provides an interface for the secondary transmission of phonons. The introduction of the periodic micro-nano structure of the interface transforms the original two-dimensional heat transfer of the diamond to metal interface into a three-dimensional heat transfer mode, thereby improving the interface heat transfer capacity and the thermal conductivity by about 20%; and the brazing material is completely filled in the periodic micro-nano structure, and the joint structure is uniform and defect-free. Regarding the improvement of the mechanical properties of the joint, the diamond / metal interface structure is prepared through laser processing. On the one hand, the stress distribution of the joint is improved and the stress concentration of the joint is relieved; on the other hand, the periodic micro-nano structure of the interface, through the crack deflection effect, prolongs the fracture path when the joint breaks in the face of external force, consumes the energy required for fracture, and improves the mechanical properties of the joint by about 30%. In addition, excessively high processing temperatures are not required to avoid severe thermal damage and cracks inside the diamond. Therefore, diamond / metal joints with uniform tissue and no defects such as cracks can have better mechanical properties and thermal conductivity at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a schematic diagram of the structure of the periodic micro-nano structure drawn on the diamond surface of Example 1;
[0020] Figure 2 This is a schematic diagram of the structure of the periodic micro-nano structure drawn on the diamond surface of Example 2;
[0021] Figure 3 This is a schematic diagram of the structure of the periodic micro-nano structure drawn on the diamond surface of Example 3;
[0022] Figure 4 Schematic diagram of the microscope of the periodic micro-nano structure drawn on the diamond surface in Example 1, Example 2 and Example 3 with a length unit of 50 μm;
[0023] Figure 5 Schematic diagram of the microscope of the periodic micro-nano structure drawn on the diamond surface in Example 1, Example 2 and Example 3 with a length unit of 10 μm;
[0024] Figure 6 for Figure 5 Schematic diagram of the microscope of the middle area with a length unit of 1 μm. DETAILED DESCRIPTION
[0025] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. Although certain embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be interpreted as being limited to the embodiments described herein. On the contrary, these embodiments are provided to provide a more thorough and complete understanding of the present invention. It should be understood that the drawings and embodiments of the present invention are only for exemplary purposes and are not intended to limit the scope of protection of the present invention.
[0026] Unless otherwise defined, all technical and scientific terms used in this application have the same meanings as those commonly understood by those skilled in the art to which this application belongs; the terms used in the specification of this application are only for the purpose of describing specific implementation methods and are not intended to limit this application;
[0027] The term "including" and its variations used in this article are open inclusions, that is, "including but not limited to"; the term "based on" is "based at least in part on"; the term "one embodiment" means "at least one embodiment"; the term "another embodiment" means "at least one other embodiment"; the term "some embodiments" means "at least some embodiments"; the term "optionally" means "optional embodiments". The relevant definitions of other terms will be given in the following description. It should be noted that the concepts of "first" and "second" mentioned in the present invention are used to distinguish different objects, rather than to describe a specific order or a primary and secondary relationship. In addition, the terms "first" and "second" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of this application, unless otherwise specified, the meaning of "multiple" is two or more.
[0028] In related technologies, the preparation of micro-nanostructure arrays at the interface helps interfacial heat conduction. Researchers have found that micro-nanostructures at the interface can be an effective way to enhance interfacial heat conduction between solids. At the same time, in the field of material manufacturing, it is generally believed that such a rough interface can also greatly improve the interfacial bonding strength of the material. Therefore, by introducing interfacial micro-nanostructures, it is expected to improve both the mechanical properties and heat transfer properties of diamond / metal joints.
[0029] In view of the problems existing in the above-mentioned related technologies, this embodiment provides a high thermal conductivity diamond / metal joint and a brazing method thereof.
[0030] An embodiment of the present invention provides a brazing method for a high thermal conductivity diamond / metal joint, comprising the following steps:
[0031] Laser processing of diamond surface to draw periodic micro-nano structures on the diamond surface;
[0032] Brazing material is coated on the surface of diamond with periodic micro-nano structure, fixed in a diamond / brazing material / metal sandwich structure, and vacuum brazing is performed to obtain a high thermal conductivity diamond / metal joint.
[0033] In this embodiment, the diamond / metal interface structure is prepared on the diamond surface by laser processing, which increases the effective contact area of the diamond / metal interface, similar to the introduction of a heat sink structure at the interface, which can achieve more efficient heat transfer at the interface. In addition, laser processing introduces a periodic micro-nano structure in the diamond ablation area during the scanning process, so that when phonons are reflected at the interface of heterogeneous materials, the side wall of the micro-nano structure provides an interface for the secondary transmission of phonons. The introduction of the periodic micro-nano structure of the interface transforms the original two-dimensional heat transfer from the diamond to the metal interface into a three-dimensional heat transfer mode, improves the interface heat transfer capacity, improves the thermal conductivity by about 20%, and the thermal conductivity is greater than 500W / (m·K); and the brazing material is completely filled in the periodic micro-nano structure, and the joint organization is uniform and defect-free.
[0034] Regarding the improvement of the mechanical properties of the joint, the diamond / metal interface structure is prepared by laser processing. On the one hand, the stress distribution of the joint is improved and the stress concentration of the joint is relieved; on the other hand, the periodic micro-nano structure of the interface, through the crack deflection effect, prolongs the fracture path when the joint breaks in the face of external force, consumes the energy required for fracture, and improves the mechanical properties of the joint. The mechanical properties are improved by about 30%, and the connection strength is ≥200Mpa. In addition, excessively high processing temperatures are not required to avoid severe thermal damage and cracks inside the diamond.
[0035] In general, diamond / metal joints with uniform structure and no defects such as cracks can have better mechanical properties and thermal conductivity.
[0036] Optionally, before the step of laser processing the diamond surface, the step further includes: cleaning of the base material, the base material includes diamond and metal, the base material is immersed in alcohol and ultrasonically cleaned for 5-10 minutes, and then taken out and dried.
[0037] In this optional embodiment, ultrasonic cleaning removes dirt, grease, corrosion products or other contaminants on the surface of the parent material.
[0038] Specifically, the base material is soaked in alcohol and placed in an ultrasonic cleaning machine for ultrasonic cleaning.
[0039] Optionally, the step of laser processing the diamond surface specifically includes: using a picosecond laser to laser process the diamond surface, wherein the laser spot diameter is 10-40 microns, the processing speed is 10-40 mm / s, the laser power is 0.5-12.5 W, and the repetition frequency is 100-400 KHz.
[0040] In this optional embodiment, the selection of various parameters in the laser processing step can obtain periodic micro-nano structures at the micron or nanometer level. From the perspective of thermal conductivity, the precision of the periodic micro-nano structures, processing defects and graphic parameters (such as specific surface area, aspect ratio, etc.) will affect the interface thermal conductivity. The provided processing parameters can achieve the thermal conductivity optimization of laser processing grooves.
[0041] Specifically, the eyepiece is focused before laser processing so that the laser spot diameter is 10-40 microns. The laser processing path is drawn using AutoCAD, and periodic micro-nano structures such as periodic micro-grooves, hole arrays, and honeycomb arrays are drawn separately according to different structures. After laser processing ablation, alcohol ultrasonic cleaning is used for 5-10 minutes and drying is performed.
[0042] Optionally, the periodic micro-nano structure is a micrometer-scale periodic structure or a nanometer-scale periodic structure, and the periodic micro-nano structure includes a periodic micro-groove or hole array or a honeycomb array.
[0043] In this optional embodiment, periodic micro-nano structures such as periodic micro-grooves, hole arrays, and honeycomb arrays enable the sidewalls of the micro-nano structures to provide an interface for the secondary transmission of phonons when phonons are reflected at the interface of dissimilar materials. The introduction of the periodic micro-nano structures of the interface transforms the original two-dimensional heat transfer from diamond to metal into a three-dimensional heat transfer mode, thereby improving the heat transfer capacity of the interface. The periodic micro-nano structures extend the fracture path when the joint breaks in the face of external force through the crack deflection effect, consume the energy required for fracture, and improve the mechanical properties of the joint.
[0044] Optionally, when the solder is in powder form, the solder is mixed with cellulose and dissolved in pine alcohol to form a paste, which is then applied to the surface of the diamond with a periodic micro-nano structure, wherein the ratio of the solder, pine alcohol and cellulose is 2:1:1-3:1:1.
[0045] In this optional embodiment, laser processing is used to prepare a diamond / metal interface structure on the diamond surface, and solder paste can be applied to the interface structure, increasing the contact area between the diamond / metal interface and the solder paste, thereby achieving more efficient heat transfer at the interface.
[0046] Specifically, the solder can be in the form of powder, foil or adhesive tape. The foil or adhesive tape can be prepared into a size as large as the diamond by cutting and applied to the diamond surface. The powder solder needs to be mixed with pine alcohol and cellulose to form a paste. The ratio of solder, pine alcohol and cellulose is 2:1:1-3:1:1. The paste solder is evenly applied to the ablation side of the diamond surface by screen printing.
[0047] Optionally, the solder is an active solder, and the solder is silver-copper-indium-titanium or silver-copper-titanium or silver-copper-tin-titanium.
[0048] In this optional embodiment, active solder is used to achieve diamond / metal interface bonding.
[0049] Optionally, the metal is aluminum or copper.
[0050] In this optional embodiment, aluminum and copper are both metals with high thermal conductivity.
[0051] Optionally, the step of fixing the diamond / brazine / metal sandwich structure specifically includes: placing the sandwich structure in a mold and applying a pressure of 0.5-4 MPa for fixing.
[0052] In this optional embodiment, after the pressure is applied, the sandwich structure of diamond / solder paste / metal will not be relatively displaced. The mold may be a graphite mold.
[0053] Optionally, vacuum brazing specifically includes placing the fixed sandwich structure into a vacuum brazing furnace for heating, wherein the vacuum brazing furnace maintains a vacuum degree of less than 10 -5 , maintain a heating rate of 10-20℃ / min, heat to 400℃ and keep warm for 5-20min, continue to maintain a heating rate of 10-20℃ / min, heat to 640℃-860℃, keep warm for 20-40min, and maintain a cooling rate of 5-10℃ / min to room temperature.
[0054] Specifically, the temperature of the second heating is 640-860°C, which is the melting point of the solder. The melting point of the silver-copper-indium-titanium solder is 640-720°C, the melting point of the silver-copper-tin-titanium solder is 720-800°C, and the melting point of the silver-copper-titanium solder is 720-860°C.
[0055] In this optional embodiment, the vacuum brazing temperature is relatively low, thereby preventing serious thermal damage and cracks inside the diamond due to high temperature.
[0056] A high thermal conductivity diamond / metal joint provided in an embodiment of the present invention is manufactured by the brazing method for a high thermal conductivity diamond / metal joint as described in any one of the above items.
[0057] In this embodiment, the connection strength between diamond and metal of the obtained high thermal conductivity diamond / metal joint is ≥200Mpa, the joint thermal conductivity is >500W / (m·K), and the structure of the high thermal conductivity diamond / metal joint is uniform without obvious defects.
[0058] The present invention is further described below in conjunction with specific embodiments.
[0059] Example 1, brazing method of high thermal conductivity diamond / metal joint.
[0060] (1) Matrix treatment: Soak the diamond block and Cu block in alcohol, put them in an ultrasonic cleaner for 5 minutes, take them out and dry them.
[0061] (2) Diamond surface laser ablation: The diamond surface is processed by a picosecond laser. The eyepiece is focused before processing, and the laser spot diameter is 10 microns. The laser processing path is drawn using AutoCAD, and periodic micro grooves are drawn separately according to different structures. The processing speed is set to 10 mm / s, the laser power is set to 0.5 W, and the repetition frequency is 100 KHz. After picosecond laser ablation, alcohol ultrasonic cleaning is used for 5 minutes and drying treatment is performed. Micron- or nanometer-level periodic micro-nano structures are drawn on the diamond surface, such as Figure 1 shown.
[0062] (3) Coating of active solder powder: Common commercial active solder silver-copper-indium-titanium foil is cut into the same size as diamond and coated on the ablation side of the diamond surface.
[0063] (4) Sample assembly: Diamond, solder, and Cu block are placed in a graphite mold according to a diamond / solder / Cu sandwich structure. The bottom of the graphite mold is fixed, and a pressure of 0.5 MPa is applied to the sandwich structure from the top.
[0064] (5) Brazing process: Place the welding structure together with the graphite mold into a vacuum brazing furnace and heat it. The vacuum degree is less than 10 -5 , the heating rate is maintained at 10℃ / min, the temperature is raised to 400℃ and kept for 5min, the heating rate is continued to be maintained at 10℃ / min, the temperature is raised to 640℃, and kept for 20min, the cooling rate is maintained at 5℃ / min, and after cooling to room temperature, a high thermal conductivity diamond / metal joint with good interface bonding can be obtained.
[0065] Example 2, brazing method of high thermal conductivity diamond / metal joint.
[0066] (1) Matrix treatment: Soak the diamond block and Cu block in alcohol, put them in an ultrasonic cleaner for 8 minutes, take them out and dry them.
[0067] (2) Diamond surface laser ablation: The diamond surface is processed by a picosecond laser. The eyepiece is focused before processing, and the laser spot diameter is 25 microns. The laser processing path is drawn using AutoCAD, and periodic micro grooves are drawn separately according to different structures. The processing speed is set to 25 mm / s, the laser power is set to 2.5 W, and the repetition frequency is 200 KHz. After picosecond laser ablation, alcohol ultrasonic cleaning is used for 8 minutes and drying treatment is performed. Micron- or nanometer-level periodic micro-nano structures are drawn on the diamond surface, such as Figure 2 shown.
[0068] (3) Coating of active solder powder: Common commercial active solder silver-copper-indium-titanium foil is cut into the same size as diamond and coated on the ablation side of the diamond surface.
[0069] (4) Sample assembly: Diamond, solder, and Cu block are placed in a graphite mold according to a diamond / solder / Cu sandwich structure. The bottom of the graphite mold is fixed and a pressure of 2 MPa is applied to the sandwich structure from the top.
[0070] (5) Brazing process: Place the welding structure together with the graphite mold into a vacuum brazing furnace and heat it. The vacuum degree is less than 10 -5 , the heating rate is maintained at 15℃ / min, the temperature is raised to 400℃ and kept for 10min, the heating rate is continued to be maintained at 15℃ / min, the temperature is raised to 680℃, and kept for 30min, the cooling rate is maintained at 8℃ / min, and after cooling to room temperature, a high thermal conductivity diamond / metal joint with good interface bonding can be obtained.
[0071] Example 3, brazing method of high thermal conductivity diamond / metal joint.
[0072] (1) Matrix treatment: Soak the diamond block and Cu block in alcohol, put them in an ultrasonic cleaner for 8 minutes, take them out and dry them.
[0073] (2) Diamond surface laser ablation: The diamond surface is processed by a picosecond laser. The eyepiece is focused before processing, and the laser spot diameter is 40 microns. The laser processing path is drawn using AutoCAD, and periodic micro grooves are drawn separately according to different structures. The processing speed is set to 40 mm / s, the laser power is set to 12.5 W, and the repetition frequency is 400 KHz. After picosecond laser ablation, alcohol ultrasonic cleaning is used for 10 minutes and drying treatment is performed. Micron- or nanometer-level periodic micro-nano structures are drawn on the diamond surface, such as Figure 3 shown.
[0074] (3) Coating of active solder powder: Common commercial active solder silver-copper-indium-titanium foil is cut into the same size as diamond and coated on the ablation side of the diamond surface.
[0075] (4) Sample assembly: Diamond, solder, and Cu block are placed in a graphite mold according to a diamond / solder / Cu sandwich structure. The bottom of the graphite mold is fixed and a pressure of 4 MPa is applied to the sandwich structure from the top.
[0076] (5) Brazing process: Place the welding structure together with the graphite mold into a vacuum brazing furnace and heat it. The vacuum degree is less than 10 -5 The heating rate is maintained at 20℃ / min, the temperature is raised to 400℃ and kept for 20min, the heating rate is continued to be maintained at 20℃ / min, the temperature is raised to 720℃, and kept for 40min, the cooling rate is maintained at 10℃ / min, and after cooling to room temperature, a high thermal conductivity diamond / metal joint with good interface bonding can be obtained.
[0077] Comparative Example 1, brazing method of diamond / metal joint.
[0078] (1) Matrix treatment: Soak the diamond block and Cu block in alcohol, put them in an ultrasonic cleaner for 5 minutes, take them out and dry them.
[0079] (2) Coating of active solder powder: Common commercial active solder silver-copper-indium-titanium foil is cut into the same size as diamond and coated on the ablation side of the diamond surface.
[0080] (3) Sample assembly: Diamond, solder, and Cu block are placed in a graphite mold according to a diamond / solder / Cu sandwich structure. The bottom of the graphite mold is fixed, and a pressure of 0.5 MPa is applied to the sandwich structure from the top.
[0081] (4) Brazing process: Place the welding structure together with the graphite mold into a vacuum brazing furnace and heat it. The vacuum degree is less than 10 -5 , the heating rate is maintained at 10℃ / min, the temperature is raised to 400℃ and kept for 5min, the heating rate is continued to be maintained at 10℃ / min, the temperature is raised to 640℃, and kept for 20min, the cooling rate is maintained at 5℃ / min, and after cooling to room temperature, a high thermal conductivity diamond / metal joint with good interface bonding can be obtained.
[0082] Comparative Example 2, brazing method of diamond / metal joint.
[0083] (1) Matrix treatment: Soak the diamond block and Cu block in alcohol, put them in an ultrasonic cleaner for 8 minutes, take them out and dry them.
[0084] (2) Coating of active solder powder: Common commercial active solder silver-copper-indium-titanium foil is cut into the same size as diamond and coated on the ablation side of the diamond surface.
[0085] (3) Sample assembly: Diamond, solder, and Cu block are placed in a graphite mold according to a diamond / solder / Cu sandwich structure. The bottom of the graphite mold is fixed and a pressure of 4 MPa is applied to the sandwich structure from the top.
[0086] (4) Brazing process: Place the welding structure together with the graphite mold into a vacuum brazing furnace and heat it. The vacuum degree is less than 10 -5 The heating rate is maintained at 20℃ / min, the temperature is raised to 400℃ and kept for 20min, the heating rate is continued to be maintained at 20℃ / min, the temperature is raised to 720℃, and kept for 40min, the cooling rate is maintained at 10℃ / min, and after cooling to room temperature, a high thermal conductivity diamond / metal joint with good interface bonding can be obtained.
[0087] Effect Example
[0088] The periodic micro-nano structures drawn on the diamond surface in Examples 1, 2 and 3 were observed when the microscope length unit was 50 μm, 10 μm and 1 μm respectively. When the microscope length unit was 50 μm, the periodic micro-nano structures in Example 1 were as follows: Figure 4 As shown in (a), the periodic micro-nanostructure of Example 2 is as follows Figure 4 As shown in (b), the periodic micro-nanostructure of Example 3 is as follows Figure 4 As shown in (c), when the microscope length unit is 10 μm, the periodic micro-nanostructure of Example 1 is as follows Figure 5 As shown in (a), Figure 5 The (d) area in (a) is enlarged to a length unit of 1 μm. Figure 6 As shown in (d), the periodic micro-nanostructure of Example 2 is as follows Figure 5 As shown in (b), Figure 5 The (e) area in (b) is enlarged to a length unit of 1 μm. Figure 6 As shown in (e), the periodic micro-nanostructure of Example 3 is as follows Figure 5 As shown in (c), Figure 5 The (f) area in (c) is enlarged to a length unit of 1 μm. Figure 6 As shown in (f).
[0089] Depend on Figures 1 to 6 It can be seen that the diamond / metal interface structure is prepared on the diamond surface by laser processing, which increases the effective contact area of the diamond / metal interface, which is similar to introducing a heat sink structure at the interface.
[0090] The thermal diffusion coefficients of the joints obtained in Example 1 and Comparative Example 1 were tested, and the thermal diffusion coefficient of the joint in Example 1 was found to be 212.1 mm 2 / s, the thermal diffusion coefficient of the joint of comparative example 1 is 191.0 mm2 / s; the shear strength of the joints obtained in Example 3 and Comparative Example 2 was tested, and the shear strength of the joint in Example 1 reached 218±7MPa, and the shear strength of the joint in Comparative Example 1 was 168±10MPa. It can be seen that the diamond / metal joint obtained by introducing a periodic micro-nano structure in the diamond ablation area during laser processing can have better mechanical properties and thermal conductivity.
[0091] Although the present invention is disclosed as above, the protection scope of the present invention is not limited thereto. Those skilled in the art may make various changes and modifications without departing from the spirit and scope of the present invention, and these changes and modifications will fall within the protection scope of the present invention.
Claims
1. A brazing method for high thermal conductivity diamond / metal joints, characterized in that: The following steps are involved: Laser processing a diamond surface to draw a periodic micro-nano structure on the diamond surface; Brazing material is coated on the diamond surface with the periodic micro-nano structure, fixed according to the sandwich structure of diamond / brazing material / metal, and vacuum brazing is performed to obtain a high thermal conductivity diamond / metal joint.
2. The brazing method of high thermal conductivity diamond / metal joint according to claim 1, characterized in that: Before the step of laser processing the diamond surface, the method further includes the step of cleaning the base material, wherein the base material includes diamond and metal, the base material is immersed in alcohol and ultrasonically cleaned for 5-10 minutes, and then taken out and dried.
3. The brazing method of high thermal conductivity diamond / metal joint according to claim 1, characterized in that: The step of laser processing the diamond surface specifically includes: using a picosecond laser to laser process the diamond surface, wherein the laser spot diameter is 10-40 microns, the processing speed is 10-40 mm / s, the laser power is 0.5-12.5 W, and the repetition frequency is 100-400 KHz.
4. The brazing method of high thermal conductivity diamond / metal joint according to claim 1, characterized in that: The periodic micro-nano structure is a periodic structure of micrometer scale or a periodic structure of nanometer scale, and the periodic micro-nano structure includes a periodic micro-groove or hole array or a honeycomb array.
5. The brazing method of high thermal conductivity diamond / metal joint according to claim 1, characterized in that: When the solder is in powder form, the solder is mixed with cellulose and dissolved in pine alcohol to form a paste, which is then applied to the diamond surface with the periodic micro-nano structure drawn thereon, wherein the ratio of the solder, pine alcohol and cellulose is 2:1:1-3:1:
1.
6. The brazing method of high thermal conductivity diamond / metal joint according to claim 1, characterized in that: The solder is an active solder, and the solder is silver-copper-indium-titanium or silver-copper-titanium or silver-copper-tin-titanium.
7. The brazing method of high thermal conductivity diamond / metal joint according to claim 1, characterized in that: The metal is aluminum or copper.
8. The brazing method of high thermal conductivity diamond / metal joint according to claim 1, characterized in that: The step of fixing the sandwich structure of diamond / the solder / metal specifically includes: placing the sandwich structure in a mold and applying a pressure of 0.5-4 Mpa for fixing.
9. The brazing method of high thermal conductivity diamond / metal joint according to claim 8, characterized in that: The vacuum brazing specifically includes placing the fixed sandwich structure into a vacuum brazing furnace for heating, wherein the vacuum brazing furnace maintains a vacuum degree of less than 10 -5 , maintain a heating rate of 10-20℃ / min, heat to 400℃ and keep warm for 5-20min, continue to maintain a heating rate of 10-20℃ / min, heat to 640℃-860℃, keep warm for 20-40min, and maintain a cooling rate of 5-10℃ / min to room temperature.
10. A high thermal conductivity diamond / metal joint, characterized in that: The high thermal conductivity diamond / metal joint is made by the brazing method as described in any one of claims 1 to 9.
Citation Information
Patent Citations
Processing technology for forming micro-nano multi-layer composite structure on metal surface
CN107252942A
Pretreatment method of dissimilar metal material before welding, dissimilar metal material welding product and welding method thereof
CN112620856A
Active brazing method for improving performance of graphite / copper dissimilar material joint
CN113478040A
AgCu-based brazing filler metal and method for brazing and connecting diamond and copper through AgCu-based brazing filler metal
CN114473289A
Diamond micro-nano composite structure tool for machining hydrophobic surface of workpiece and preparation method
CN114959633A
Cited By
Method for improving electromigration reliability of lead-free interconnection welding spots based on ultrafast laser processing of hexagons
CN119747782A
Welding process of high-strength cutter alloy steel and ceramic composite layer
CN121946000A